Strategi Pembangunan Kekuatan TNI di Natuna Utara Dalam Menghadapi Konflik Laut Cina Selatan (LCS) - Nopriadi, Nopriadi; Herly Dwiyanto, Herly Dwiyanto; Danuri, Danuri (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
Tensions in the Asia-Pacific region have escalated due to the aggressive actions of the People's Republic of China (PRC) regarding its South China Sea (SCS) claims. This situation has prompted regional countries to enhance their defense capabilities, further complicated by the involvement of the United States and the formation of the AUKUS pact, which has created a security dilemma. Indonesia faces several challenges in building its national defense capacity as a non-party to the direct conflict. These challenges include: (1) a relatively low defense budget allocation, less than 1% of GDP, despite its vast territory and significant maritime threats; (2) a budget focus skewed towards personnel development rather than modernizing primary weapons systems and investing in defense technology research; and (3) inconsistencies in defense procurement planning due to domestic and international political factors. To address the potential escalation of the SCS conflict, Indonesia requires a national defense strategy that can act as a balance of power in the region. This study employs a qualitative method with a descriptive-analytical approach, utilizing primary (interviews) and secondary data. The findings reveal that VUCA conditions, geographical challenges, and an Indonesia-centric development vision influence Indonesia's defense strategy. The Archipelago Defense Strategy (SPN), formulated by the Ministry of Defense and the Indonesian Armed Forces (TNI), prioritizes the Large Islands Strategy and the development of forward bases in Natuna to counteract the PRC's aggression in the SCS.